Prebiotic Route to Thymine from Formamide—A Combined Experimental–Theoretical Study - Lukáš Petera; Klaudia Mrazikova; Lukas Nejdl; Kristyna Zemankova; Marketa Vaculovicova; Adam Pastorek; Svatopluk Civis; Petr Kubelik; Alan Heays; Giuseppe Cassone; Jiri Sponer; Martin Ferus; et al. (Molecules, 2021)
Synthesis of RNA nucleobases from formamide is one of the recurring topics of prebiotic chemistry research. Earlier reports suggest that thymine, the substitute for uracil in DNA, may also be synthesized from formamide in the presence of catalysts enabling conversion of formamide to formaldehyde. In the current paper, we show that to a lesser extent conversion of uracil to thymine may occur even in the absence of catalysts. This is enabled by the presence of formic acid in the reaction mixture that forms as the hydrolysis product of formamide. Under the reaction conditions of our study, the disproportionation of formic acid may produce formaldehyde that hydroxymethylates uracil in the first step of the conversion process. The experiments are supplemented by quantum chemical modeling of the reaction pathway, supporting the plausibility of the mechanism suggested by Saladino and coworkers.